2000
DOI: 10.1108/09544780010341969
|View full text |Cite
|
Sign up to set email alerts
|

Employee involvement and quality management

Abstract: This paper records the research on the investigation of the empirical relationship between employee involvement (EI) and quality management. It is based on data from a survey of 180 manufacturing companies. The main findings are: EI is positively correlated with total quality management (TQM) enablers; EI is positively correlated with improvements in business performance; EI positively influences the contribution of TQM to the improvement of business performance; EI is marginally related to ISO registration; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…The influence of employees' involvement and empowerment on firms' changing processes has been extensively reported in the literature, which strongly highlight its importance and potential for organisational changes (Sun, Hui, Tam, & Frick, 2000;Welikala & Sohal, 2008) through a personal involvement in problem-solving and decision-making. However, although the terms are sometimes used interchangeably, the concepts are distinct in nature, even if some researchers claim that they may overlap somehow (Lashley, 1999;Watson, 1986).…”
Section: About Empowermentmentioning
confidence: 99%
“…The influence of employees' involvement and empowerment on firms' changing processes has been extensively reported in the literature, which strongly highlight its importance and potential for organisational changes (Sun, Hui, Tam, & Frick, 2000;Welikala & Sohal, 2008) through a personal involvement in problem-solving and decision-making. However, although the terms are sometimes used interchangeably, the concepts are distinct in nature, even if some researchers claim that they may overlap somehow (Lashley, 1999;Watson, 1986).…”
Section: About Empowermentmentioning
confidence: 99%
“…Ladrgson et al (2010) reported that, 'It is important that all employees' feel they can demonstrate initiative and that they have the responsibility to enact changes and influence activities in their own area of work'. Therefore, it is vital to empower employees to make them active participant in a quality environment, which is in fact intrinsically at the heart of the QM concept (Sun et al, 2000).…”
Section: Influencementioning
confidence: 99%
“…Receiving an innovation subsidy can provide SMEs with the financial resources to allow their employees to invest more time in innovation (George, 2005). Confirming a positive influence of innovation subsidies on employee involvement would provide policy makers with a new rationale for subsidy programs, because employee involvement has positive effects on organizational change, performance, and employee satisfaction (Caves and Porter, 1977;Denison, 1984;Mendes, 2012;Porter, 1979;Pun and Chin, 1999;Sun et al, 2000;Welikala and Sohal, 2008;Wilkinson, 1998). Following this line of reasoning, I dedicate Chapter 2 to testing for a relationship between receiving an innovation subsidy and employee involvement.…”
Section: H a P T E R 1 Innovation In Smes: A Multi-actor Perspectivementioning
confidence: 99%
“…Employee involvement is the extent to which employees take part in the strategic decision-making process (Amah and Ahiauzu, 2013;Pun et al, 2001). It drives organizational change and performance (Mendes, 2012;Sun et al, 2000;Welikala and Sohal, 2008;Wilkinson, 1998). For example, including employees in the decision-making process as members of strategic groups prompts enduring changes in firm profitability and organizational effectiveness (Caves and Porter, 1977;Porter, 1979).…”
Section: Employee Involvement and Slack Resourcesmentioning
confidence: 99%
See 1 more Smart Citation